Exploring the Elements of Organizational Inertia and Impacts on Organization - Suhaimi Mohd Yusof, Muhammad; Rahim Romle, Abd (International Journal of Psychosocial Rehabilitation, 2020)
Previous studies on inertia indicated the word inertia in Latin means “idle and lazy,” and it is always referred to to describe difficulties faced by organizations in implementing changes within n organizations. As inertia became a part of the routines in organizations, organizations tend to practice the same routines and resist changes due to their past experience. Inertia is a form of inability to resist changes either in processes or procedures within an organization, and it could be either individual or organizational. Literature reviews explained the development of organizational inertia, elements, and impacts on organizations.